A Systematic Review : The Effectiveness of Nebulizer Inhalation Therapy in Increasing Oxygen Saturation in Patients with Acute Respiratory Failure - Martanti, Yuniar Dwi; Purnawan, Iwan (Universitas Malahayati, 2025)
ABSTRACTAcute respiratory failure is a critical condition that necessitates prompt intervention to improve oxygen saturation and prevent further complications. Nebulizer inhalation therapy is widely used to deliver medications directly to the respiratory tract, enhancing oxygenation and alleviating respiratory distress. This systematic review aims to evaluate the effectiveness of nebulizer inhalation therapy in improving oxygen saturation and overall clinical outcomes in patients with acute respiratory failure. Using the keywords